Diversity and Biogeography of Human Oral Saliva Microbial Communities Revealed by the Earth Microbiome Project - Wang, Jinlan; Feng, Jianqing; Zhu, Yongbao; Li, Dandan; Wang, Jianing; Chi, Weiwei (Frontiers in Microbiology, 2022)
The oral cavity is an important window for microbial communication between the environment and the human body. The oral microbiome plays an important role in human health. However, compared to the gut microbiome, the oral microbiome has been poorly explored. Here, we analyzed 404 datasets from human oral saliva samples published by the Earth Microbiome Project and compared them with 815 samples from the human gut, nose/pharynx, and skin. The diversity of the human saliva microbiome varied significantly among individuals, and the community compositions were complex and diverse. The saliva microbiome showed the lowest species diversity among the 4 environment types. Human oral habitats shared a small core bacterial community containing only 14 operational taxonomic units under 5 phyla, which occupied over 75% of the sequence abundance. For the 4 habitats, the core taxa of the saliva microbiome had the greatest impact on saliva habitats than other habitats and were mostly unique. In addition, the saliva microbiome showed significant differences in the populations of different regions, which may be determined by the living environment and lifestyle/dietary habits. Finally, the correlation analysis showed high similarity between the saliva microbiome and the microbiomes of Aerosol (non-saline) and Surface (non-saline), i.e., two environment types closely related to human, suggesting that contact and shared environment being the driving factors of microbial transmission. Together, these findings expand our understanding of human oral diversity and biogeography.